Variasi Dialek Bahasa Manggarai Dalam Tuturan Penjual Dan Pembeli di Pasar Wae Kesambi Kecamatan Komodo Kabupaten Manggarai Barat - Rosmini Rosmini; Andi Syukri Syamsuri; Desi Ayuandira (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2023)
This study examines the forms of variations of the Manggarai dialect found in the speech of sellers and buyers at Wae Kesambi Market, Jalan Palmerah Selatan, Komodo District, Labuan Bajo City, West Manggarai Regency and describes the functions of variations in the Manggarai dialect in the speeches of sellers and buyers at Pasar Wae Kesambi, Jalan Palmerah Selatan. Komodo District, Labuan Bajo City, West Manggarai Regency. The theory used in this study is the theory put forward by Chaer and Agustina (210), Halliday and Alwasilah (1993) relating to language variations and the functions of language variations. This research took place at Wae Kesambi Market, Jalan Palmerah Selatan, Komodo District, Labuan Bajo City, West Manggarai Regency. Data was collected using observation techniques, recording techniques, listening techniques and note-taking techniques. The results showed that there were 74 data on dialect variations of the Manggarai language with details on language variations in terms of 15 speakers, 2 data on language variations in terms of usage, 2 data on language variations in terms of formality and 74 data on terms of facilities. oral means. The research also shows the results of the dialect variation function of the Manggarai language which consists of 74 data in the form of 2 data of instrumental functions, 1 data of toris regulatory functions, 2 data of representational functions, 7 data of interactional functions, 1 data of personal functions and 1 data of heuristic functions. .